2003
DOI: 10.1074/jbc.m212407200
|View full text |Cite
|
Sign up to set email alerts
|

Direct Demonstration of Involvement of Protein Kinase Cα in the Ca2+-induced Platelet Aggregation

Abstract: Platelets play critical roles in hemostasis and thrombosis through their aggregation following activation of integrin ␣ IIb ␤ 3 . However, the molecular mechanism of the integrin activation inside platelets remains largely unknown. Pharmacological experiments have demonstrated that protein kinase C (PKC) plays an important role in platelet aggregation. Because PKC inhibitors can have multiple substrates and given that non-PKC-phorbol ester-binding signaling molecules have been demonstrated to play important ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 41 publications
3
34
0
Order By: Relevance
“…This is in agreement with previous biochemical evidence suggesting an essential role for PKCα in regulating integrin (18). Importantly also, genome-wide association analysis of coronary artery disease revealed a cluster of SNPs in the PRKCA gene, with a maximal P value association of just over 10 -3 (SNP rs12600582) (34,35).…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…This is in agreement with previous biochemical evidence suggesting an essential role for PKCα in regulating integrin (18). Importantly also, genome-wide association analysis of coronary artery disease revealed a cluster of SNPs in the PRKCA gene, with a maximal P value association of just over 10 -3 (SNP rs12600582) (34,35).…”
Section: Introductionsupporting
confidence: 79%
“…The study by Han et al (33) elegantly showed that PKCα was required for integrin α IIb β 3 activation in a reconstituted cell system rather than in the platelet. The study by Tabuchi et al (18) used an in vitro permeabilized platelet system to investigate receptor-independent calcium-mediated activation of platelet aggregation. Although this latter study demonstrated that added purified PKCα was able to support a calcium-induced platelet aggregation response, the approach has limitations in that receptor-mediated activation is lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,49 PLCg2 is a central enzyme in inducing the production of second messengers inositol (1,4,5)-trisphosphate and diacylglycerol leading to raised levels of intracellular calcium and activation of PKC which can positively regulate a-and dense-granule secretion in platelets as well as platelet aggregation. 41,50 Inhibition of PLC in our studies significantly reduced aggregation and secretion (Figure 6), indicating that an FcgRIIa-Syk-PLCg signaling pathway is activated. In contrast, we observed that BAPTA, a calcium chelator, has no significant effect on platelet secretion responses, suggesting that calcium is not required.…”
Section: Discussionmentioning
confidence: 96%
“…Platelet aggregation and a-granule releases are regulated, in part, by protein kinase C (PKC) signaling (Yoshioka et al, 2001;Tabuchi et al, 2003;Chari et al, 2009;Konopatskaya et al, 2009;Gilio et al, 2010). The PKC isoenzymes are a family of serine/threonine protein kinases that are subdivided into three classes, including the conventional (a, bI, bII, g), novel (d, «, h, u), and atypical (l,i, m,j) PKCs.…”
Section: Introductionmentioning
confidence: 99%